A Study of Visual Aesthetics in Social Advertising: A Case Study of an Environmental Awareness Campaign in Pilanggede Balen Village, Bojonegoro: Kajian Estetika Visual dalam Iklan Sosial: Studi Kasus Kampanye Kesadaran Lingkungan di Desa Pilanggede Balen Bojonegoro - Rofiqoh, Yusnia I’anatur; H, M. Lukmanul; Arfa, Dhagastani Fairuza; Pratama, Bagas Aditya (Academia Open, 2023)
This study analyses visual aesthetics in social advertisements in an environmental awareness campaign in Pilanggede Village, Balen Subdistrict, Bojonegoro Regency. This village is known for actively educating the community through visual media such as posters, billboards, and public service videos. Using a descriptive qualitative approach, this study employs observation, interviews, and documentation. Design elements such as colour, typography, illustration, and composition are analysed to assess their influence on the effectiveness of the campaign message. Green and blue colours are predominantly used to create associations with nature and cleanliness, while local illustrations reinforce the context of the message. Simple typography is used to ensure readability. This study finds that visual aesthetics plays an important role in attracting attention and influencing community attitudes. Community involvement in the creation of campaign materials increases the effectiveness of the message. However, limited resources and understanding of design are major challenges. This study suggests improving local design capacity and cross-sector collaboration to optimise the results of visual campaigns at the village level. Highlights: Design Impact – Visual elements boost message clarity and engagement. Community Role – Involving locals strengthens message relevance. Key Challenges – Limited resources and design skills hinder effectiveness. Keywords: Visual Aesthetics, Social Advertising, Environmental Campaigns, Visual Communication, Ecological Awareness, Community Participation.